A Head-to-Head Comparison of Augmented Wealth in Germany and the United States - Timm Bönke; Markus M. Grabka; Carsten Schröder; Edward N. Wolff (The Scandinavian Journal of Economics, 2020)
We examine the composition of augmented household wealth (i.e., the sum of net worth and pension wealth) in the United States and Germany. Pension wealth makes up a considerable portion of household wealth, of about 48 percent in the United States and 61 percent in Germany. When pension wealth is included in household wealth, the Gini coefficient falls from 0.889 to 0.700 in the United States, and from 0.755 to 0.508 in Germany. If the wealth shares in Germany were the same as in the United States, this would lead to a 12.6 percent increase in the Gini coefficient in the augmented wealth distribution in Germany.
Keywords: D31; H55; J32; 330; Augmented wealth; net worth; pension wealth; Socio-Economic Panel; Survey of Consumer Finances